A positive correlation between bacterial autoaggregation and biofilm formation in native Sinorhizobium meliloti isolates from Argentina - Sorroche, F.G. (2012)
Sinorhizobium meliloti is a symbiotic nitrogen-fixing bacterium that elicits nodule formation on roots of alfalfa plants. S. meliloti produces two exopolysaccharides (EPSs), termed EPS I and EPS II, that are both able to promote symbiosis. EPS I and EPS II are secreted in two major fractions that reflect differing degrees of subunit polymerization, designated high- and low-molecularweight fractions. We reported previously that EPSs are crucial for autoaggregation and biofilm formation in S. meliloti reference strains and isogenic mutants. However, the previous observations were obtained by use of "domesticated" laboratory strains, with mutations resulting from successive passages under unnatural conditions, as has been documented for reference strain Rm1021. In the present study, we analyzed the autoaggregation and biofilm formation abilities of native S. meliloti strains isolated from root nodules of alfalfa plants grown in four regions of Argentina. 16S rRNA gene analysis of all the native isolates revealed a high degree of identity with reference S. meliloti strains. PCR analysis of the expR gene of all the isolates showed that, as in the case of reference strain Rm8530, this gene is not interrupted by an insertion sequence (IS) element. A positive correlation was found between autoaggregation and biofilm formation abilities in these rhizobia, indicating that both processes depend on the same physical adhesive forces. Extracellular complementation experiments using mutants of the native strains showed that autoaggregation was dependent on EPS II production. Our results indicate that a functional EPS II synthetic pathway and its proper regulation are essential for cell-cell interactions and surface attachment of S. meliloti. © 2012, American Society for Microbiology.